1997
DOI: 10.1104/pp.114.1.275
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of the Ascorbate-Glutathione Cycle in Mitochondria and Peroxisomes of Pea Leaves

Abstract: l h e presence of the enzymes of the ascorbate-glutathione cycle was investigated in mitochondria and peroxisomes purified from pea (Pisum sativum L.) leaves. AI1 four enzymes, ascorbate peroxidase (APX; EC 1.1 1.1.1 l ) , monodehydroascorbate reductase (EC 1.6.5.4), dehydroascorbate reductase (EC 1.8.5.1), and glutathione reductase (EC 1.6.4.2), were present in mitochondria and peroxisomes, as well as i n the antioxidants ascorbate and glutathione. l h e activity of the ascorbate-glutathione cycle enzymes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
519
0
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 754 publications
(549 citation statements)
references
References 43 publications
16
519
0
14
Order By: Relevance
“…Peroxisomes contain enzymatic and nonenzymatic defense mechanisms to deal with different types of ROS such as O 2 .2 and H 2 O 2 . The enzymes involved in these mechanisms include superoxide dismutases, catalase, and components of the ascorbate-glutathione cycle (ascorbate, glutathione, and ascorbate peroxidase as well as dehydroascorbate, monodehydroascorbate, and glutathione reductase; Jiménez et al, 1997;Sandalio and Romero-Puertas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisomes contain enzymatic and nonenzymatic defense mechanisms to deal with different types of ROS such as O 2 .2 and H 2 O 2 . The enzymes involved in these mechanisms include superoxide dismutases, catalase, and components of the ascorbate-glutathione cycle (ascorbate, glutathione, and ascorbate peroxidase as well as dehydroascorbate, monodehydroascorbate, and glutathione reductase; Jiménez et al, 1997;Sandalio and Romero-Puertas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Monodehydroascorbate reductase is ubiquitous in all the phylogenetic groups and its isoforms existing in chloroplasts (Hossain et al 1984), cytosol (Dalton et al 1993), peroxisomes and mitochondria (Jimenez et al 1997) have been reported. The activity of MDAR has been shown to be up-regulated under several stress conditions, for instance in tomato by salinity stress (Mittova et al 2003) and high light intensity (Gechev et al 2003), in rice by low temperature (Oidaira et al 2000), and in Arabidopsis by UV-C exposure (Kubo et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This fact is of some importance since the expected increase in H # O # as a result of the SOD reaction was accompanied by an increased enzymatic capacity to decompose it. Considering that in pea leaves most of the ASC-GSH cycle enzymes is between chloroplasts and cytosol (Gillham & Dodges 1986 ;Edwards et al, 1990 ;Mittler & Zilinskas, 1994 ;Jime! nez et al, 1997a), our results suggest that in NaCl-treated leaves and in both cell compartments, the N # O # generated by increased FeSOD and CuZn-SODs I and II could be removed by APX and MDHAR.…”
Section:   mentioning
confidence: 99%